2022
DOI: 10.1111/aogs.14411
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term surgical outcomes of nerve‐sparing discoid and segmental resection for deep endometriosis

Abstract: Introduction The aim of this study was to investigate long‐term outcomes in terms of pain, quality of life (QoL), and gastrointestinal symptoms in women following colorectal surgery for deep endometriosis. Material and methods In this historical cohort, women who underwent surgical treatment for deep endometriosis by either nerve‐sparing full‐thickness discoid resection (DR) or colorectal segmental resection (SR) between March 2011 and August 2016 were re‐evaluated through telephone interviews about their long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(62 reference statements)
2
3
1
Order By: Relevance
“…Although surgery was generally associated with an improvement in dyspareunia, as already reported by several authors, 34–36 we observed an overall worsening of sexual function, even though it was not statistically significant. This finding might depend on the high number of posterolateral parametrectomies performed in association with segmental bowel resection (78.7% of patients) and on the median distance of resection from the anal margin (6 cm).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although surgery was generally associated with an improvement in dyspareunia, as already reported by several authors, 34–36 we observed an overall worsening of sexual function, even though it was not statistically significant. This finding might depend on the high number of posterolateral parametrectomies performed in association with segmental bowel resection (78.7% of patients) and on the median distance of resection from the anal margin (6 cm).…”
Section: Discussionsupporting
confidence: 74%
“…31,32 In addition, in a recent study on discoid resection for bowel DE, Roman et al reported a significant improvement in gastrointestinal function only regarding the GIQLI but not with all validated questionnaires used before and after surgery (KESS, Wexner score, and Bristol scale), though their findings are not reliably comparable due to the absence of segmental resections in his series. 33 Although surgery was generally associated with an improvement in dyspareunia, as already reported by several authors, [34][35][36] we ob- median distance of resection from the anal margin (6 cm). Both of these factors can lead to the lesion of a number of autonomic nerves responsible for decreasing blood flow to the vagina and aiding lubrication, as previously reported.…”
Section: Discussionsupporting
confidence: 60%
“…Colorectal deep endometriosis (DE) is commonly associated with more pain and adverse gastrointestinal (GI) outcomes 2,3 . Although a large percentage of women with colorectal DE can be managed conservatively, 4 several studies have demonstrated a significant short‐ but also long‐term decrease in pain symptoms following surgical resection of colorectal DE 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although a large percentage of women with colorectal DE can be managed conservatively, 4 several studies have demonstrated a significant short-but also long-term decrease in pain symptoms following surgical resection of colorectal DE. [5][6][7][8] There is, so far, no real consensus on how to optimally treat colorectal endometriosis surgically, since the application of the main three techniques, namely, segmental colorectal resection, full thickness discoid resection (FTDR) and so-called shaving, depends on various factors which may differ from unit to unit and surgeon to surgeon. 9,10 These include infiltration length and depth of DE, presence of multifocal disease and surgical experience and personal preference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation